Globalisation and the Colonising State of Mind - Jackson, Moana (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: colonisation; globalisation; neoliberalism; protest

The balance destroyed: the consequences for Māori women of the colonisation of Tikanga Māori - Mikaere, Annabel (Published Jointly by the International Research Institute for Māori and Indigenous Education and Ani Mikaere, 2003)
Keywords: colonisation; crown law; european influences; mana wāhine; sexism; social conditions; social life and customs; wāhine māori

The changing images of nineteenth century Māori society: from tribes to nation - Henare, Manuka Arnold (2003)
Keywords: colonisation; he whakaputanga; history; self-determination; thesis; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Chapter 18: The Treaty of Waitangi and Recognition of Tikanga Māori - Mikaere, Ani (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land tenure; law; race relations; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi

The face behind the law: The United Nations and the rights of indigenous peoples - Jackson, Moana (Yearbook of New Zealand jurisprudence, 2005)
In recent years Maori people have adopted many strategies to protect and advance the well being and visions implicit in the exercise of tino rangatiratanga. Much of that work has been done at home, but an increasing number of Iwi and other Maori organisations are now participating in international affairs that are seen to have some relevance to our lives. They are joining a worldwide movement by Indigenous Peoples to reassert their rights and reclaim their rightful place.
Keywords: UNDRIP; civil Rights; colonisation; crown law; imperialism; international law; international organization; racism; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Authenticating Mäori Physicality: Translations of ‘Games’ and ‘Pastimes’ by Early Travellers and Missionaries to New Zealand - Hokowhitu, Brendan (The International Journal of the History of Sport, 2008)
This paper theorizes how knowledge of indigenous tribal epistemologies was made ‘knowable’ through Enlightenment rationalism in an early colonial context. Specifically, the paper determines how and what knowledge of Mäori tribal physical activities was interpreted and authenticated through early travellers' tales and missionaries’ accounts in New Zealand. The central thesis argues that what was established as authentic and truthful aligned with Enlightenment rationalism, while those Mäori physical practices incomprehensible to Western understandings were deemed inauthentic and, consequently, were obscured and/or discarded. Throughout, the article theorizes the translation of knowledge into meaningful Western discourses and how these translations came to be crystallized in the colonial imagination.
Keywords: colonisation; cultural practices

Chapter Four: The Treaty of Waitangi in the Postcolonial Era - Walker, Ranginui (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land march; land tenure; post-colonialism; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Tino rangatiratanga : water under the bridge? - Bargh, Maria (He pūkenga kōrero: a journal of Māori studies, 2007)
Argues that Māori have been actively engaged in practising tino rangatiratanga in various forms even since before the Declaration of Independence ...
Keywords: colonisation; constitution; government; international relations; iwi; kaitiakitanga; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; water rights

Returning the indigenous to the centre: a view from Aotearoa/New Zealand - DeSouza, Ruth; Cormack, Donna (Diversity in Health and Social Care, 2009)
Keywords: colonisation; discrimination; identity; māori rights; social aspects; social justice